Design of Surface Drainage System for Managing Water Congestion in Mahanadi Delta: A Case Study - Paul, J. C.; Panigrahi, B.; Behera, B. P.; Patnaik, P.K. (Journal of Agricultural Engineering, 2014)
A suitable design of surface drainage system for managing water logging in lowland rice areas in the Mahanadi delta of coastal Odisha is proposed. In order to estimate the appropriate drainage coefficient and runoff, probability analysis was made for 21 years daily rainfall data and used in different methods. Drainage coefficients were computed as 45.0, 26.9, 31.7 and 360.6 mm.day-1 by Simplified Hydrologic procedure, SCS-Curve Number method, Cypress- Creak formula and Rational formula, respectively. The drainage coefficient computed by SCS-Curve Number method was the best fit value for the study area and was adopted for design of surface drainage system with 7-day storm and 8-year return period. Accordingly, the design discharge for surface drainage system was computed as 0.6 m3.s-1 using SCS-CN method, and peak discharge was estimated to be 6.7 m3.s-1 using Rational formula suitable for the design of the channel and the outfall structure, respectively. Manning’s formula for channel design and different design formulae were adopted for computation of dimensions of the broad-crested drop spillway serving as the outfall structure. The estimated cost was found well within the prescribed norms.